Healthy lifestyle: some limitations of biomedical focus - Pinzón Gómez, Daniel (2013)
This article remarks some limitations that healthy lifestyles offer to biomedical speech, which centers its argument on individual behavior of people; it alsoemphasizes investigations in Adventists of developed countries and the lack of randomized studies with this population in outlying countries. At the same time, it establishes the necessity to analyze the restrictions of healthy lifestyle, taking into account the contributions of social epidemiology, particularly in the context of social determinants. Finally, it mentions the importance of reducing inequity in health, as well as the necessity of theoretical contributions from other disciplinesto understand health and its connection with healthy lifestyles beyond the biomedical focus.